Today tonight tomorrow ebook - Solomon, Rachel Lynn (Today Tonight Tomorrow, 2020)
"Brilliant, hilarious, and oh-so-romantic." — BuzzFeed "Swoony, steamy." — Entertainment Weekly The Hating Game meets Booksmart by way of Morgan Matson in this unforgettable romantic comedy about two rival overachievers whose relationship completely transforms over the course of twenty-four hours. Today, she hates him. It's the last day of senior year. Rowan Roth and Neil McNair have been bitter rivals for all of high school, clashing on test scores, student council elections, and even gym class pull-up contests. While Rowan, who secretly wants to write romance novels, is anxious about the future, she'd love to beat her infuriating nemesis one last time. Tonight, she puts up with him. When Neil is named valedictorian, Rowan has only one chance at victory: Howl, a senior class game that takes them all over Seattle, a farewell tour of the city she loves. But after learning a group of seniors is out to get them, she and Neil reluctantly decide to team up until they're the last players left—and then they'll destroy each other. As Rowan spends more time with Neil, she realizes he's much more than the awkward linguistics nerd she's sparred with for the past four years. And, perhaps, this boy she claims to despise might actually be the boy of her dreams. Tomorrow...maybe she's already fallen for him.